2021
DOI: 10.1097/aog.0000000000004569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Coronavirus Disease 2019 (COVID-19) Pandemic on Delays in and Barriers to Abortion

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is associated with delays in and barriers to accessing abortion, which are associated with higher gestational ages at the time of abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…La saturation des hôpitaux par les malades COVID-19 en période de crise sanitaire pourrait avoir laissé peu de place pour les autres patients, particulièrement ceux mobilisant une équipe d'anesthésistes comme c'est le cas pour les IVG instrumentales sous AG. D'autre études ont également rapporté des difficultés d'accès à l'IVG pour des grossesses dont l’âge gestationnel était avancé [25] . Atay H. et al.…”
Section: Discussionunclassified
“…La saturation des hôpitaux par les malades COVID-19 en période de crise sanitaire pourrait avoir laissé peu de place pour les autres patients, particulièrement ceux mobilisant une équipe d'anesthésistes comme c'est le cas pour les IVG instrumentales sous AG. D'autre études ont également rapporté des difficultés d'accès à l'IVG pour des grossesses dont l’âge gestationnel était avancé [25] . Atay H. et al.…”
Section: Discussionunclassified
“…Burgeoning literature examines COVID-19 era abortion bans, documenting several negative impacts of the bans, especially related to travel time, wait time, cost, safety, and the disproportionate impact on young, Black, and Latinx pregnant people (Dahl et al 2021;Fang and Perler 2021;Hill et al 2021;Roberts et al 2021). Several scholars have pointed towards increased accessibility of telehealth and medication abortion as potential workarounds for these restrictions (Awowole and Ijarotimi 2022;Chong et al 2021;Karlin et al 2021).…”
mentioning
confidence: 99%
“…These bans were passed while Roe and Casey were still the major precedent, and they ultimately impacted thousands of people. The pandemic exposed pre-existing structural inequalities and restricting abortion access placed a further, disproportionate burden on pregnant people of color(Jones et al 2020;McCloskey et al 2021;Nandagiri, Coast, and Strong 2020) Dahl et al (2021). found that COVID-19 restrictions impacted Black and Latinx people's access to abortion in Illinois by increasing wait times and, gestational stage of pregnancy.Their research highlights additional burdens in states where second trimester abortions are expensive and difficult to obtain.…”
mentioning
confidence: 99%